Age and sex differences in associations between self-reported health, physical function, mental function and mortality. (January 2022) - Lin, Ming-Hsien; Chen, Li-Ju; Huang, Shih-Tsung; Meng, Lin-Chieh; Lee, Wei-Ju; Peng, Li-Ning; Hsiao, Fei-Yuan; Chen, Liang-Kung
Highlights: Age- and sex-specific approaches to explore health, physical and mental function and clinical outcomes with a life-course approach have become critical determinants to promote healthy and successful aging. Although the self-reported health status was similar across different age- and sex-stratified subgroups, older women self-report higher levels of difficulty with physical movement and with the instrumental activities of daily living (IADL) than middle-aged men. An increased risk of depression was found in middle-age and older women but not in older men. Abstract: Objectives: To explore how age and sex affect the impacts of self-rated health, self-reported physical activities, physical function, and depressive symptoms on long-term mortality among community-dwelling middle-aged and older adults using a nationally representative population-based cohort study. Methods: Data from 1550 study participants from the Social Environment and Biomarkers of Aging Study (SEBAS) were retrieved for analysis, and all participants were divided into four groups based on their age and gender. Middle aged participants were aged 53 to 64 years, and elderly subjects were ≥ 65 years old. Multivariate logistic regression models were applied to investigate the associations between age, sex, and self-reported disabilities of physical activities, physical function (activities of daily living (ADL) and instrumental activities of daily living (IADL) and depression. Results: Although the self-reported health status was similar across different age- and sex-stratified subgroups, older women were at the highest risk in self-reported difficulty with physical activities (aOR 2.58 [1.55-4.28]) and difficulty with IADL (aOR 3.32 [2.20-5.03]) compared to men. After adjusting for living arrangement, residence locale, education levels, occupation, socioeconomic status, self-reported health, multimorbidity, impairments in daily activities, and depressive symptoms, older men were found to display the highest risk of mortality (aHR 2.06 [95% CI 1.45-2.93]). Conclusions: Although self-reported health was similar across different age and sex stratified subgroups, women (particularly older women) are significantly more likely to have worse physical and functional health than men. After adjusting for all confounding factors, men are at substantially greater risk for mortality despite reporting better health and functional performance.